Frontiers of diversity : explorations in contemporary pluralism - Plaw, Avery (Amsterdam ; New York : Rodopi, 2005)
Frontiers of Diversity critically examines the explanatory and normative power of pluralism in contemporary philosophy, politics, economics and culture. Based on the papers presented at the "First Global Conference on Critical Issues in Pluralism" at Mansfield College, Oxford, it brings together for the first time essays examining pluralism's impact, both positive and negative, in each of these critical domains. These essays exhibit something of the fertility of the concept of pluralism, not only across the spectrum of fields, but at all levels of analysis, from individual to social to nationa.
Acknowledgements; Introduction; PART I Philosophical Pluralism; A Defense of Tolerance as a Moral Virtue; Is Monotheism Compatible with Pluralism? Reflections on Richard Rorty's Critique of Religion; Political Philosophy and Pluralism in a Globalised World; PART II Political Pluralism; Pluralist Imperialism: The Emergent Paradigm of U.S. Foreign Policy; Value-Pluralism and Human Rights; Discourses on Immigration in South Africa: Managing Diversity in a New Nation; PART III Economic Pluralism; Dollarization: The End of Monetary Pluralism in Latin America?; The FDI Space Heterogeneity.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Cultural pluralism; Globalization; Diversité culturelle; Mondialisation; globalism; SOCIAL SCIENCE -- Discrimination & Race Relations; Cultural pluralism; Globalization; Pluralismus